INDIGENOUS PEOPLE: EMANCIPATORY POSSIBILITIES IN CURRICULUM DEVELOPMENT - McMurchy‐Pilkington, Colleen; Pikiao, Ngati; Rongomai, Nagati (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
In this article, I argue that emancipatory possibilities for Mäori, the Indigenous people of New Zealand, rely on structural changes that enable them to have control over resources, decision making, and meaning, and that emancipation is a journey traveled by oppressed groups as they exercise their collective agency. The 1990s development of Pängarau, the national mathematics curriculum policy in the medium of Mäori, provides the context for this discussion. Recent developments indicate that state structures have shifted towards giving Mäori more control in curriculum writing. Key words: collective agency, state structures, Indigenous curriculum development, New Zealand education, Mäori education, mathematics education Dans cet article, l’auteure soutient que les possibilités d’émancipation des Maori, le peuple autochtone de la Nouvelle‐Zélande, reposent sur des changements structu‐ raux qui leur permettent d’avoir la haute main sur des ressources, la prise de déci‐ sions et l’orientation générale et que l’émancipation est un chemin parcouru par des groupes opprimés qui exercent une action collective. L’élaboration dans les années 1990 de Pängarau, la politique nationale relative à l’enseignement des mathématiques en maori, fournit le contexte de l’analyse présentée ici. Des faits récents indiquent que les structures de l’État évoluent vers la remise d’un contrôle accru aux Maori pour ce qui est de l’élaboration des programmes d’études. Mots clés : action collective, structures étatiques, élaboration de programmes d’études par des autochtones, éducation en Nouvelle‐Zélande, éducation dispensée aux Maori, enseignement des mathématiques